Antiproliferative properties of the USF family of helix-loop-helix transcription factors. - Luo, X (1996)
USF is a family of transcription factors characterized by a highly conserved basic-helix-loop-helix-leucine zipper (bHLH-zip) DNA-binding domain. Two different USF genes, termed USF1 and USF2, are ubiquitously expressed in both humans and mice. The USF1 and USF2 proteins contain highly divergent transcriptional activation domains but share extensive homologies in the bHLH-zip region and recognize the same CACGTG DNA motifs. Although the DNA-binding and transcriptional activities of these proteins have been characterized, the biological function of USF is not well understood. Here, focus- and colony-formation assays were used to investigate the potential involvement of USF in the regulation of cellular transformation and proliferation. Both USF1 and USF2 inhibited the transformation of rat embryo fibroblasts mediated by Ras and c-Myc, a bHLH-zip transcription factor that also binds CACGTG motifs. DNA binding was required but not fully sufficient for inhibition of Myc-dependent transformation by USF, since deletion mutants containing only the DNA-binding domains of USF1 or USF2 produced partial inhibition. While the effect of USF1 was selective for Myc-dependent transformation, wild-type USF2 exerted in addition a strong inhibition of E1A-mediated transformation and a strong suppression of HeLa cell colony formation. These results suggest that members of the USF family may serve as negative regulators of cellular proliferation in two ways, one by antagonizing the transforming function of Myc, the other through a more general growth-inhibitory effect.